Lung function impairment in relation to asbestos-induced pleural lesions with reference to the extent of the lesions and the initial parenchymal fibrosis - Lebedová, Jindřiška; Dlouhá, Beatrica; Rychlá, Lenka; Neuwirth, Jirí; Brabec, Marek; Pelclová, Daniela; Fenclová, Zdenka (Scandinavian Journal of Work, Environment & Health, 2003)
' ' OBJECTIVES ': 'The study focused on the effect of pleural lesions on the lung function of asbestos-exposed workers. ' ' METHODS ': 'A clinical check-up, chest radiography, high-resolution computed tomography (HRCT), and lung function testing were performed on 162 asbestos-exposed workers without any sign of parenchymal fibrosis on their chest radiographs. According to the HRCT scans, two subgroups were delineated, 97 subjects with pleural lesions and 65 referents without pleural lesions. Four categories of pleural lesions were specified according to the extent. Parenchymal changes, if identified on the HRCT scans, were recorded. ' ' RESULTS ': 'The radiographic sensitivity and specificity for pleural lesion detection when compared with that of HRCT were 64.9% and 98.5%, respectively. The HRCT scans showed parenchymal abnormalities in 46.3% of the participants, more frequently in those with pleural lesions (67.0% versus 15.4%, P<0.0001). After the effect of parenchymal fibrosis was taken into account, pleural lesions were found to have a significant effect on the decrease in total lung capacity, forced vital capacity, and forced expiratory volume in 1 second, if being classified into category 2 or higher. ' ' CONCLUSIONS ': 'Pleural lesions proved to have a negative effect on lung function, depending on their extent. The effect of the initial parenchymal fibrosis detectable in the HRCT scans only was also significant. A normal chest radiograph does not exclude the presence of pleural lesions or initial parenchymal fibrosis, with a possible negative effect on lung function.
Keywords: asbestos exposure; asbestos-induced pleural lesion; asbestosis; lung function impairment; parenchymal fibrosis; pleural change; pleural thickening; ventilation impairment